2017
DOI: 10.1002/ptr.5878
|View full text |Cite
|
Sign up to set email alerts
|

Rutin, a Quercetin Glycoside, Restores Chemosensitivity in Human Breast Cancer Cells

Abstract: Several studies have documented the ability of flavonoids to sensitize cancer cells to chemotherapeutics and reverse multidrug resistance by inhibition of efflux pumps (adenosine triphosphate-binding cassette transporters), apoptosis activation, and cell cycle arrest. In this study, the flavonoid rutin (quercetin 3-O-β-d-rutinoside) was investigated as chemosensitizer towards two different human epithelial breast cancer cell lines: (i) MB-MDA-231, selected as representative for triple-negative breast cancer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(86 citation statements)
references
References 27 publications
(36 reference statements)
3
76
0
Order By: Relevance
“…In this field, natural plant compounds such as flavonoids and stilbenes have received great attention, with the majority (e.g. curcumin, naringenin) reported to show promising anti-tumor activity in preclinical studies [5,22,41,42]. However, bioactive plant compounds have poor bioavailability and poor solubility, which reduce their efficacy in clinical studies [5,7,41,43].…”
Section: Oscc Nano-based Chemopreventionmentioning
confidence: 99%
“…In this field, natural plant compounds such as flavonoids and stilbenes have received great attention, with the majority (e.g. curcumin, naringenin) reported to show promising anti-tumor activity in preclinical studies [5,22,41,42]. However, bioactive plant compounds have poor bioavailability and poor solubility, which reduce their efficacy in clinical studies [5,7,41,43].…”
Section: Oscc Nano-based Chemopreventionmentioning
confidence: 99%
“…Flavonoids are classified into the following subclasses: anthocyanins, flavanols, flavanones, flavonols, flavonones, and isoflavones (Amarowicz et al, ; Kabera et al, ; Kumar & Pandey, ). A wide range of pharmacological activities, including antioxidant, antibacterial, hepatoprotective, antinflammatory, and antihyperlipidemic effect, are attributed to flavonoids (Abenavoli et al, ; Azzini et al, ; Belwal, Nabavi, Nabavi, & Habtemariam, ; D'Evoli et al, ; Farhadi, Khameneh, Iranshahi, & Iranshahy, ; Farhat, Drummond, & Al‐Dujaili, ; Iriti et al, ; Miccadei et al, ; Ninfali, Antonini, Frati, & Scarpa, ; Rasouli, Mohammad‐Bagher Hosseini‐Ghazvini, & Khodarahmi, ; Rees, Dodd, & Spencer, ; Riccio et al, ; Tungmunnithum, Thongboonyou, Pholboon, & Yangsabai, ). The term flavonoid generally indicates a phenol compound having a phenylbenzopyran chemical structure with a carbon skeleton of a C6–C3–C6 joined to a chroman ring (Pereira, Valentão, Pereira, & Andrade, ).…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Rutin (3,3í,4í,5,7-pentahydroxyflavone-3-rhamnoglucoside), a flavonol, is found in large quantities in passionflower, buckwheat, tea, and apple and possess a variety of pharmacological activities, like antioxidant, cytoprotective, vasoprotective, anticarcinogenic, neuroprotective and cardioprotective (20)(21)(22)(23)(24)(25)(26). Rutin was also reported to stimulate apoptosis in human breast cancer cells, whereas reinstating the chemosensitivity of HER2 negative and triple-negative breast cancer cells (27). Elsayed et al reported that rutin prevents the activity c-Met kinase in TNBC cells thus considerably reducing the growth of TNBC MDA-MB-231/GFP orthotopic xenografts in murine models (28).…”
Section: Vanadium-rutin Complex Sensitizes Breast Cancer Cellsmentioning
confidence: 99%